professional ethics of Interrogator - Mahmoud Yousefvand; Mohammad Mahdi Yousefvand (اخلاق وحیانی, 2023)
There is an ethical framework for the profession of an investigator in criminal justice systems. Present adaptation has focused on the comparative investigation of interrogator's ethics in Iranian law by studying jurisprudence and ethics foundations, and it is a qualitative research with a comparative approach, which is in terms of practical goals and in terms of documentary and library research tools.The collected information includes the analysis of Iranian criminal laws and jurisprudence sources.According to the research findings in Iranian law, the interrogator, like many jobs and professions, has ethical rules; In case of violation of moral laws, in addition to violation of fair proceedings and lack of respect for human dignity, it causes torment of the interrogator's conscience and has a guarantee of material and social enforcement. The result of the interrogator's ethics is a fair trial and respecting the human dignity of the accused. Non-observance of moral values for the interrogator leads to otherworldly punishment, and in Iranian law, sometimes punishment and in some cases compensation to the accused.